A dynamic analysis of regional R&D efficiency. The case of Italian and Spanish regions - Ricardo AGUADO; Jabier Martinez; Massimo Cermelli (European Regional Science Association (ERSA), 2013)
Research and Development activities are key elements in the search of more productive economic outcomes, the generation of new economic sectors and, in general, of a better economic performance at the micro and macro levels. In many European countries, the responsibility of the design and implementation of R&D policies is shifting from the national level to the regional level, making the regional level a relevant field of analysis. Spain and Italy are examples of this progressive change. At the same time, the financial, economic and social crisis that is affecting the countries situated in the periphery of the eurozone is reducing the budget for R&D activities that firms, universities, public administrations and other institutions can devote to this issue. Again, Spain and Italy are clear examples of economic difficulties and diminishing public and private budgets. In this context, it is crucial to assess and measure the efficiency of all kind of expenditures, especially the ones that are directly linked with the achievement of a more competitive economy. In this way, regions achieving more efficiency should be granted with more funding or, alternatively, not efficient regions should adapt efficient R&D policies to their own institutional and social backgrounds. In this paper we will use the DEA (Data Envelopment Analysis) methodology in order to measure at the regional level the efficiency ratio between R&D inputs and the outcomes achieved. DEA methodology compares the amount of inputs used with the outcomes achieved, ordering regions in terms of productivity, not in terms of absolute values. Following this path, the best ranked region will be the one that minimizes the use of inputs maximizing the amount of outputs. Results over time will be discussed and regions will be grouped according to their efficiency level and their evolution in this field over time. Comparisons between regions will be made at the national level (Italian regions on one side and Spanish regions on the other) and also adding all regions from the two countries. Typologies of regions according to their efficiency levels will be outlined and justified. The paper will conclude with some policy recommendations for each group of regions, so that regions can design policies and adopt measures in order to improve their efficiency and their overall results regarding R&D.
Keywords: 330; R&D efficiency; DEA; regional analysis; Spain; Italy